Increasing Environmental Awareness to Overcome Lack of Natural Resources Through Character Building Based on Microeconomic Theory - Febianti, Yopi Nisa; Putri, Dian Permana (International Research-Based Education Journal, 2019)
This research aims to assess students awareness attitude on natural resources in the region of Unswagati Cirebon Indonesia. Qualitative research method is used in this study involving 87 students as sample at the second grade of Economic Education FKIP Unswagati in the year of 2016/2017. Data were gathered using interviews, observation, and documents. These were analyzed employing qualitative technique through developing the domains, taxonomies, compositions, and cultural themes. Results indicate that the students have positive attitudes towards their environment while using natural resources, having sufficient knowledge and skills in maintaining, managing, preserving, and restoring the environment to overcome the lack of natural resources.Keywords: Environmental awareness, natural resources, character building, microeconomic theory